Herpetofaunal Diversity in Nagarjun Forest - Pokhrel, Ganesh K; Aryal, Prakash C; Shah, Karan B; Rijal, Bishal; Suwal, Madan K; Kharel, Subash C; Paudel, Evanath; Dhamala, Man K (Nepal Journal of Science and Technology, 2012)
The composition of amphibians and reptiles diversity in the Nagarjun forest of Shivapuri Nagarjun National Park was studied. Purposive transect and opportunistic survey methods were adopted to estimate species diversity. The species caught during survey were identified on the spot using field guide and released in-situ. Transects were distributed across six distinct micro-watersheds in the forest. In total, 134 individuals belonging to 11 species were observed. The spatial distribution patterns of the species were also mapped. The condition and potential threat of the habitat is also assessed during this study. DOI: http://dx.doi.org/10.3126/njst.v12i0.6524 Nepal Journal of Science and Technology 12 (2011) 358-365